Thyroid Storm Post-Radioactive Iodine Therapy - Hardina, Septi; Budiawan, Hendra (RSUP Dr. Kariadi, 2023)
Background Thyroid storm is an endocrine disorder emergency which has a high morbidity and mortality rates. The incidence of thyroid storm is seen in less than 10% of all hospitalized thyrotoxicosis patients. However, it has a high mortality rate, which accounts to 20-30% of the cases. It is important to diagnose early to facilitate appropriate immediate management, which can improve prognosis and clinical outcome in patients. Thyroid storm usually begins with precipitating factor. Thyroid storm precipitated by radioactive iodine therapy is rare. Case Report We report a rare case in a 28 year old female patient. Patient came with complaints of palpitations, nausea without vomiting, fever, >3x diarrhea, and shortness of breath after radioactive iodine therapy. The clinical presentation of thyroid storm is polymorphic that becomes a diagnostic problem as it can delay treatment and increase the risk of mortality. It is important to suspect a thyroid storm based on the patient's clinical presentation, because the diagnosis of thyroid storm is based more on the patient's clinical presentation. The existence of the Burch-Wartofsky scoring system facilitates the diagnosis of a thyroid storm. The total Burch-Wartofsky score in this patient based on the clinical presentation is 45, which is highly suggestive of thyroid storm. Conclusion Thyroid storm precipitated by radioactive iodine therapy is rare. The incidence of thyroid storm after administration of radioactive iodine therapy is 0.34 percent. Precipitating factors other than the administration of radioactive iodine therapy such as infection and discontinuation of antithyroid drug therapy can trigger a thyroid storm.